Improving Students' Critical Thinking Skills through the STEM Digital Book - Rusilowati, Ani; Lisdiana, Lisdiana; A’yun, Qurrota (Journal of Innovative Science Education, 2020)
One of the 21st century life skills that needs to be developed in the education process is critical thinking skills. The importance of being trained in critical thinking skills in learning science is motivated by the results of the 2015 PISA test. critical thinking as 'the correct way of assessing statements' and 'reasonable reflective thinking focused on deciding what to believe or do'. In this study, indicators of critical thinking skills measured are providing simple explanations, building basic skills, providing further explanations, and concluding. One potential learning approach to help students become actively involved in learning activities and be able to improve critical thinking skills is the STEM approach. The purpose of this research is to develop a STEM approach digital book with certain characteristics, determine its validity, its practicality, and its effectiveness of the product towards improving students' critical thinking skills. This study uses a development plan from Sugiyono. The subjects of this research are the 8th graders of SMPN 26 Semarang, academic year 2019/2020. The sample as an experimental class (the product is applied in the learning process) is VIII B class, and the control class (used ordinary textbooks) is VIII D class. Data analysis techniques used in this study include descriptive data analysis related to the validity and practicality of the product, while to find out the effectiveness of the product used a normalized N-gain test and a two-sample t-test. Results show that (1) the characteristics of the digital book contained all components of the STEM approach which included aspects of science, technology, engineering, and mathematics (2) the developed digital book has valid criteria regarding to the material, media and language aspects (3) digital book developed effectively to improve students' critical thinking skills, and (4) the practicality of using digital book is considered very good by students and teachers).